On the statistical convergence of metric-valued sequences - Kucukaslan, M.; Deger, U.; Dovgoshey, O. (Український математичний журнал, 2014)
We study the conditions for the density of a subsequence of a statistically convergent sequence under which this subsequence is also statistically convergent. Some sufficient conditions of this type and almost converse necessary conditions are obtained in the setting of general metric spaces.